Effect of women economic empowerment on socio-economic development of Kabale Municipality, Uganda - Uwamahoro, Deborah; Asiimwe, Judith Bijurenda; Mwazuna, Alice Ngele (African Journal of Empirical Research, 2025)
Women's economic empowerment has become a foundation for development strategies, and it has increasingly been recognised for its important role in the socio-economic development of many countries. This study examined the effect of women’s economic empowerment on socio-economic development in Kabale Municipality, Uganda. The study was anchored on Sen’s Capability Approach theory and the Human Development Theory. A cross-sectional survey design employing a quantitative approach was adopted to evaluate relationships between the study variables at a single point in time. A sample of 153 respondents was selected from a total population of 203 using the stratified random sampling technique. Primary data was collected using structured questionnaires and analysed using descriptive and regression statistics on SPSS Version 25.0. Quantitative findings presented through descriptive statistics and regressions revealed that women’s economic empowerment positively affects socio-economic development (R²= 0.763 and p= 0.000≤ 0.005). The study concluded that economic empowerment of women positively and significantly contributes to socio-economic development in Kabale Municipality. Finally, the study recommended that efforts to empower women across the economic dimensions be prioritised to enhance socio-economic growth in the region.